#TITLE_ALTERNATIVE# - FALAH (NIM : 10108075); Pembimbing : Dr. Novriana Sumarti, MIFTAKHUL
Bank Indonesia is a financial institution authority which is responsible to achieve and maintain currency stability in Indonesia. Every commercial bank must obey the regulations stated by Bank Indonesia and one of them is known as reserve requirement (GWM). A profound explanation of the GWM contained in Peraturan Bank Indonesia Nomor 12/19/PBI/2010. The amount of GWM that must be paid is affected by the volume of deposits and loans of the bank and involves the calculation of GWM Loan to Deposit Ratio (LDR). A government bond in bank assets is a liquidity tool for its operations. The government bond interest rates affects the behavior of banks in managing liquidity. This thesis will build the dynamics system of deposits and loans volume based on the Monti-Klein models and then calculate the GWM LDR with different values of government bond interest rates. By observing the behavior of the graph generated from the model, it is observed that the greater the interest rates of government bond, the greater GWM that must be stored in Bank Indonesia.